Efficacy and safety of once-daily single-inhaler triple therapy for mild-to-moderate chronic obstructive pulmonary disease: a study protocol for a randomised and interventional study - Hiromasa Inoue; Ayako Takamori; Atsushi Kawaguchi; Takashi Kinoshita; Kazuhiro Yatera; Koichiro Takahashi; Tomotaka Kawayama; Hiroki Tashiro; Koichi Takagi; Kei Yamasaki; Kentaro Machida (BMJ Open Respiratory Research)
Introduction Bronchodilators, including long-acting muscarinic antagonists (LAMA) and long-acting beta 2 agonists (LABA), are the main treatments for chronic obstructive pulmonary disease (COPD). The efficacy of triple therapy (inhaled corticosteroids/LAMA/LABA) has also been reported. However, the effect of triple therapy on patients with mild-to-moderate COPD has not yet been clarified. This study aims to investigate the safety and efficacy of triple therapy, compared with LAMA/LABA combination therapy, for lung function and health-related quality of life in patients with mild-to-moderate COPD and identify baseline characteristics and biomarkers to predict responders and non-responders to triple therapy.Methods and analysis This is a multicentre, prospective, open-label, randomised, parallel-group study. Mild-to-moderate patients with COPD will be randomised to receive fluticasone furoate/umeclidinium/vilanterol or umeclidinium/vilanterol for 24 weeks. A total of 668 patients will be enrolled from March 2022 to September 2023 from 38 sites in Japan. The primary endpoint is the change in the trough forced expiration volume in 1 s after 12 weeks of treatment. Secondary endpoints are responder rates based on the COPD assessment test score and the St. George’s Respiratory Questionnaire total score after 24 weeks of treatment. The safety endpoint is the occurrence of any adverse events. We will also investigate safety in terms of changes in microbial colonisation in sputum and antimycobacterium avium complex antibodies.Ethics and dissemination The study protocol and informed consent documents were approved by the Saga University Clinical Research Review Board (approval number: CRB7180010). Written informed consent will be obtained from all patients. Recruitment of the patients began in March 2022. The results will be disseminated through scientific peer-reviewed publications and domestic and international medical conferences.Trial registration numbers UMIN000046812 and jRCTs031190008.